Impact of iron overload on interleukin-10 levels, biochemical parameters and oxidative stress in patients with sickle cell anemia - Barbosa, Maritza Cavalcante (Associação Brasileira de Hematologia e Hemoterapia, 2013)
OBJECTIVE: The aim of this study was to evaluate the impact of iron overload on the profile of interleukin-10 levels, biochemical parameters and oxidative stress in sickle cell anemia patients. METHODS: A cross-sectional study was performed of 30 patients with molecular diagnosis of sickle cell anemia. Patients were stratified into two groups, according to the presence of iron overload: Iron overload (n = 15) and Non-iron overload (n = 15). Biochemical analyses were performed utilizing the Wiener CM 200 automatic analyzer. The interleukin-10 level was measured by capture ELISA using the BD OptEIAT commercial kit. Oxidative stress parameters were determined by spectrophotometry. Statistical analysis was performed using GraphPad Prism software (version 5.0) and statistical significance was established for p-values < 0.05 in all analyses. RESULTS: Biochemical analysis revealed significant elevations in the levels of uric acid, triglycerides, very low-density lipoprotein (VLDL), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), urea and creatinine in the Iron overload Group compared to the Non-iron overload Group and significant decreases in the high-density lipoprotein (HDL) and low-density lipoprotein (LDL). Ferritin levels correlated positively with uric acid concentrations (p-value < 0.05). The Iron overload Group showed lower interleukin-10 levels and catalase activity and higher nitrite and malondialdehyde levels compared with the Non-iron overload Group. CONCLUSION: The results of this study are important to develop further consistent studies that evaluate the effect of iron overload on the inflammatory profile and oxidative stress of patients with sickle cell anemia.